1994
DOI: 10.1108/00197859410073664
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Comprehensive View of the Case Method in Management Development

Abstract: Hypothesizes numerous views of what a case study is and what outcomes case studies, as aids to the management development process, might be expected to facilitate. Presents a configuration of case design characteristics which, together with the accompanying discussion, is intended to be helpful to would‐be case designers and case teachers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 4 publications
0
21
0
8
Order By: Relevance
“…Specifically, officers indicated that the module made them think about the Tripwire scenario in a way different from a way in which they would usually approach the scenario. Because one objective of case method instruction is to encourage students to broaden their thinking and challenge their perspectives (Crittenden, Crittenden, & Hawes, 1999;Jennings, 1996;Kreber, 2001;Richardson, 1994;Stewart & Dougherty, 1993), these findings are encouraging.…”
Section: Research On Axlnetmentioning
confidence: 58%
See 1 more Smart Citation
“…Specifically, officers indicated that the module made them think about the Tripwire scenario in a way different from a way in which they would usually approach the scenario. Because one objective of case method instruction is to encourage students to broaden their thinking and challenge their perspectives (Crittenden, Crittenden, & Hawes, 1999;Jennings, 1996;Kreber, 2001;Richardson, 1994;Stewart & Dougherty, 1993), these findings are encouraging.…”
Section: Research On Axlnetmentioning
confidence: 58%
“…Thus, a good case for exploring military leadership issues should not only incorporate the technical and tactical backdrop in which many leadership challenges occur, but also requires sufficient character development and description of character behavior to capture the interpersonal dynamics of a situation. Because many nuances of interpersonal behavior (e.g., nonverbal behavior, personality, motivation) may be inadequately described in a narrative or "paper-based" case, it has been suggested that the film medium may be better suited for leadership cases (Richardson, 1994).…”
Section: What Makes a Good Case?mentioning
confidence: 99%
“…The literature on OM teaching points to "a lack of practical and professional skills development" (Morris, 1997, p42) (Visich & Khumawala, 2006, p1). Richardson (1994) notes that published text based cases, whilst being professionally presented and well structured, provide little assistance to those who are developing skills as "information gatherers". Mintzberg (1990) makes a similar argument in his discussion of Strategic Management.…”
Section: Skill Developmentmentioning
confidence: 99%
“…The idea of using movies as case studies to demonstrate concepts or stimulate critical thinking is not new or unique (e.g., Cavalier & Weber, 2002;Green & Cotlar, 1973a;Leeper, 1993;Richardson, 1994;Sprau, 2001). Filmed case studies offer several advantages over traditional paper cases.…”
Section: Axl Case Studiesmentioning
confidence: 99%
“…First, AXL is a form of case method instruction, which is widely hailed as an effective approach for developing critical thinking, problem solving, and interpersonal skills (e.g., Crittenden, Crittenden, & Hawes, 1999;Hassall, Lewis, & Broadbent, 1998;Jennings, 1996;Kreber, 2001;Richardson, 1994;Stewart & Dougherty, 1993). AXL instruction includes realistic, multifaceted cases and focuses on helping leaders learn "how to think" rather than "what to think," thereby preparing leaders to deal with complexity when they encounter it in their work environment (Hannafin, J. Hill, & Land, 1997;Jonassen, 2002;Lesgold, 2001).…”
Section: Theoretical Underpinnings Of Axlmentioning
confidence: 99%